Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages Notifying Accidents and Diseases The Factories Act makes it compulsory to notify certain accidents and certain illnesses. Section 64 states: 1. Where any accident occurs in a factory which either— (a) causes loss of life to a person employed in that factory; or (b) disables any such person for more than three days from earning full wages at the work at which he was employed; written notice of the accident, in the prescribed form and accompanied by the prescribed particulars, shall forthwith be sent to the inspector for the district. Apart from accidents, the general practitioner attending or called in to visit a patient, whom he believes to be suffering from one of certain diseases contracted in any factory, must notify the Chief Inspector of Factories on Form 303. The diseases are Lead, Phosphorus, Manganese, Arsenical, Mercurial, Carbon Bisulphide, Aniline, or Chronic Benzene Poisoning, or Toxic Jaundice, Toxic Anaemia, Compressed Air Illness, Anthrax, Epitheliomatous or Chrome Ulceration, contracted in a factory, or Lead Poisoning contracted in or in connection with the painting of any building. The Factories Act entitles the Secretary of State concerned, under Section 68, to "direct a formal investigation into any accident or case of disease contracted in the factory." It is just as well for the workers to know this about accidents and diseases, because there are undoubtedly occasions arising when such a formal investigation might be of considerable value, and might not always be undertaken unless pressed for. Compensation for Injuries The rights of a workman incapacitated through his employment are indirectly associated with his health and the statutory provisions for health and safety. Readers will know something of the complexity of the law relating to a workman's right to compensation. It may be well, however, to emphasize certain aspects of the matter.* The Workmen's Compensation Acts provide compensation for all accidents arising out of and in the course of the employment and in the case of incapacity the compensation is a weekly payment during incapacity. The Acts do not provide anything for loss of wages, hospital or other expenses, or for pain and suffering or loss of limb. The workman cannot, under the Acts, compel an *A full explanation of the position is given in "Workmen's Compensation," by W. H. Thompson, Solicitor (L.R.D., 1s.). 21 21/2049